Charakterystyka profilu ekonomicznego sektora bezpośredniej sprzedaży produktów rolniczych - Woźniak, Leszek; Dziedzic, Sylwia (Characteristic of Economic Profile in the Agricultural Products Direct Sales Sector, 2008)
The work presents a detailed analysis of competitive setting from agricultural product direct sales sector with the use of such a method as an economic sector profile.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 438-443